2021
DOI: 10.3390/educsci11100598
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Procedural Knowledge on the Formation of Declarative Knowledge: How Accomplishing Activities Designed for Developing Learning Skills Impacts Teachers’ Knowledge of Learning Skills

Abstract: In addition to content knowledge, it is necessary to teach learning skills. Using relevant learning skills assures better learning outcomes and abilities for the whole life course. Due to a packed curriculum or teachers having insufficient skills, student learning skills are often neglected. The aim of this study is to find out whether it is possible to support the development of declarative knowledge in learning skills in teachers through procedural knowledge acquired via practical teaching activities. A quas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…According to Saks et al. (2021, p. 2), “the development of procedural knowledge is related to the development of declarative knowledge.” Procedural knowledge is manifested in people's performance and skills and in company activities.…”
Section: Organizational Learning In Pdpmentioning
confidence: 99%
“…According to Saks et al. (2021, p. 2), “the development of procedural knowledge is related to the development of declarative knowledge.” Procedural knowledge is manifested in people's performance and skills and in company activities.…”
Section: Organizational Learning In Pdpmentioning
confidence: 99%
“…By the type of knowledge that is transferred. This position corresponds to Saks et al (2021) and is made up of various categories: content, declarative actions, procedural actions, metacognition, as well as literal, vertical, lateral, reverse, proportional, and relational learning. 4.…”
Section: Knowledge Transfer As a Teaching And Learning Processmentioning
confidence: 99%
“…Despite efforts to improve educational quality, the system revealed a significant barrier to student achievement and performance in science subjects, particularly physics (Amadalo & Musasia, 2016;Ogunleye, 2019;Pavešić, 2019) .All of the studies revealed the importance of paying close attention to students' physics knowledge at every level of the educational pyramid. Numerous studies from throughout the world suggested that students' physics performance had declined (Saks et al, 2021) and that they did not enjoy learning the subject (Taştan, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The reports of national learning assessments reveal that students' academic achievement is alarmingly declining at both lower and higher levels of education (Poljak & Jakić, 2017;Saks et al, 2021;Ses et al, 2020). Similar trends were observed when Regional Education Bureaus (REBs) conducted similar assessments regionally (REB, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation